Evaluation of the 2015 AGA guidelines on pancreatic cystic neoplasms in a large surgically confirmed multicenter cohort - Ge, Phillip S.; Muthusamy, V. Raman; Gaddam, Srinivas; Jaiyeola, Diana-Marie; Kim, Stephen; Sedarat, Alireza; Donahue, Timothy R.; Hosford, Lindsay; Wilson, Robert H.; Grande, David P.; Keswani, Rajesh N.; Kushnir, Vladimir M.; Mullady, Daniel; Edmundowicz, Steven A.; Early, Dayna S.; Komanduri, Srinadh; Wani, Sachin; Watson, Rabindra R. (Endoscopy International Open, 2017)
Background and study aims The American Gastroenterological Association (AGA) recently published guidelines for the management of asymptomatic pancreatic cystic neoplasms (PCNs). We aimed to evaluate the diagnostic characteristics of the AGA guidelines in appropriately recommending surgery for malignant PCNs.Patients and methods A retrospective multicenter study was performed of patients who underwent endoscopic ultrasound (EUS) for evaluation of PCNs who ultimately underwent surgical resection from 2004 – 2014. Demographics, EUS characteristics, fine-needle aspiration (FNA) results, type of resection, and final pathologic diagnosis were recorded. Patients were categorized into 2 groups (surgery or surveillance) based on what the AGA guidelines would have recommended. Performance characteristics for the diagnosis of cancer or high-grade dysplasia (HGD) on surgical pathology were calculated.Results Three hundred patients underwent surgical resection for PCNs, of whom the AGA guidelines would have recommended surgery in 121 (40.3 %) and surveillance in 179 (59.7 %) patients. Among patients recommended for surgery, 45 (37.2 %) had cancer, whereas 76 (62.8 %) had no cancer/HGD. Among patients recommended for surveillance, 170 (95.0 %) had no cancer/HGD; however, 9 (5.0 %) patients had cancer that would have been missed. For the finding of cancer/HGD on surgical pathology, the AGA guidelines had 83.3 % sensitivity (95 % CI 70.7 – 92.1), 69.1 % specificity (95 % CI 62.9 – 74.8), 37.2 % positive predictive value (95 % CI 28.6 – 46.4), 95.0 % negative predictive value (95 % CI 90.7 – 97.7), and 71.7 % accuracy (95 % CI 67.4 – 74.6).Conclusions The 2015 AGA guidelines would have resulted in 60 % fewer patients being referred for surgical resection, and accurately recommended surveillance in 95 % of patients with asymptomatic PCNs. Future prospective studies are required to validate these guidelines.Meeting presentations: Presented in part at Digestive Diseases Week 2016